Tensile and Compressive Behavior of Sansevieria Fiber Composites: Perilaku Tarik dan Tekan Komposit Serat Sansevieria - Al-Amin , Achmad Nurfadil; Widodo, Edi (Indonesian Journal of Innovation Studies, 2025)
General Background: Natural fiber reinforced composites have gained attention in mechanical engineering due to their lightweight characteristics and sustainable material potential. Specific Background: Sansevieria fiber combined with polyester resin and alkali treatment has demonstrated promising mechanical properties; however, limited studies evaluate the addition of amylum starch concentration within the matrix system. Knowledge Gap: There remains insufficient experimental evidence regarding how varying amylum manihot concentrations modify tensile and compressive responses of Sansevieria fiber reinforced composites. Aims: This study investigates tensile strength and compressive strength of alkali-treated Sansevieria fiber composites with 6%, 7%, 8%, 9%, and 10% amylum starch addition using ASTM D-638 and ASTM D-695 standards. Results: Experimental findings indicate that starch addition increases tensile strength, with the highest tensile stress of 35.53 MPa at 8% concentration, while compressive strength decreases, with the highest compressive stress of 108.27 MPa observed in specimens without starch addition. Novelty: The research presents a systematic comparison of dual mechanical properties under controlled starch concentration variations in polyester-based Sansevieria composites. Implications: The findings provide reference data for optimizing composition design in natural fiber reinforced composite applications requiring tailored tensile and compressive performance. Keywords: Natural Fiber Composite, Sansevieria Fiber, Amylum Starch, Tensile Strength, Compressive Strength Key Findings Highlights Maximum tensile stress recorded at 8% starch concentration. Highest compressive stress obtained in specimens without additive. Alkali-treated fiber composites show contrasting mechanical trends.